EVALUASI SISTEM DRAINASE TERHADAP GENANGAN DI KECAMATAN WATES KABUPATEN BLITAR - Marcos Amaral De Jesus Fatima; Suhudi . (BUANA SAINS, 2014)
Phond that happened in Wates Street Blitar City reached height of ±20 cm and duration of the pond was ±30 minutes. This condition resulted in broken traffic band and people took a longer other band. One of the generated impact of the existence of the pond was the demage on hard surface of the street. The final goal of this activity was in order that drainage network system can perform well in a long time according to the plan so that it can endure evaluated from construction facet and its function. The method used was by analysing flood discharge that happened (Qa max) 1,129 m3/s and channel capacity existing (Qke min) 0,014 m3/s, hereinafter evaluated and its channel capacity in handling the problem of flood can be conducted by dimension repeat channel. Dimension of channel plan in the form of square. Final result of analysis showed Qa < Qkr, the flood will not happed and capacity control (ΔQ) = 9.3 %